Insecticide Residues in Market Samples of Vegetables and Method of their Decontamination - SanthoshKumar S R (Department of Agricultural Entomology, College of Agriculture, 1997)
An investigation was undertaken to assess the insecticide residues in market samples of vegetables, viz, bittergourd, cowpea, cucumber and snakegourd from four markets of Thiruvananthapuram during three seasons of 1995. The effect of certain decontamination practices on vegetables to remove residues of insecticides was also assessed. The study revealed that organophosphate insecticides, VIZ., methyl parathion, quinalphos, monocrotophos, phosphamidon and phorate were the contaminants present in the vegetable samples. It was observed that invariably all the 288 samples collected from the four vegetable markets / (Aralumoodu, Chalai, Neduamangadu and Powdikonam) were contaminated with one or other OP insecticides. The samples collected from Aralumoodu market during the first season (January-Mar eh) and from Chalai market during the second season (Apri-May) were found contaminated to a significantly higher extent than those collected from the other three markets. The overall analysis of the data on the extent of contamination revealed that cowpea was the most contaminated vegetable. Forty three per cent of the cowpea samples were contaminated with OP insecticides above MRL followed by cucumber (25 0 %), snakegourd (22.3 %) and bittergourd (16.7 %) Among the five OP insecticides detected during the